Strategies of physiological, morpho-anatomical and biochemical adaptation in seedlings of native species exposed to mining waste - Heredia, Belén; Diaz Recio, Pablo; Young, Brian Jonathan; Pacheco, Pablo; Barcelo Zungre, Franco; Hruby, Silvina Anabela; Acevedo, Maria Andreína; Mercado, María Inés; Roqueiro, Gonzalo (Elsevier, 2025)
Seeds of four native species of trees and shrubs (Larrea cuneifolia, Bulnesia retama, Plectrocarpa tetracantha and Prosopis flexuosa) were exposed to soil contaminated with As, Cu, Cd, and Zn from an abandoned gold mine to identify adaptation strategies. Several physiological, morpho-anatomical, and biochemical parameters were determined. The seed germination of L. cuneifolia, B. retama, and P. tetracantha was fully inhibited in 100 % contaminated soil. Toxicological endpoints as NOEC, LOEC and IC50 ranged from 10 % to 25 % of soil contaminated with mining waste. Radicle elongation was the most sensitive variable to high metal(loid) con centrations, except for L. cuneifolia that hypocotyl elongation was the most affected parameter. P. flexuosa was selected to evaluate biochemical biomarkers and morpho-anatomical parameters. It showed an increase in radicle diameter and central radicle cylinder. A concentration-dependent increase in the O2 ⋅- production was observed in radicle and cotyledon. A peak of the enzymatic activity of guaiacol peroxidase, ascorbate peroxidase and catalase enzymes in P. flexuosa seedlings showed a negative relationship between metal(loid) concentration and exposure time. After a drop in the enzymatic activity, an increase in the malondialdehyde content (lipid peroxidation) was observed. The tested native species could be useful for phytoremediation of soils with a very high degree of metal contamination. A further investigation should focus on strategies to improve soil physi cochemical characteristics for plant survival at highest contamination levels